2016
DOI: 10.1093/pm/pnv066
|View full text |Cite
|
Sign up to set email alerts
|

Pain and Functionality Following Sternotomy: A Prospective 12-Month Observational Study

Abstract: This study highlights the need for further research to investigate whether more intensive pain management in the post-discharge period following sternotomy as well as the early identification of patients with neuropathic pain symptoms can reduce the incidence of persistent post-operative pain at 12 months.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…Comorbid conditions complicate and cause functional and emotional impairment in the daily life of men and women following cardiac surgery. 3 , 4 In our sample, both men and women reported associated back/neck problems, depression, and persistent pain intensity with lower HRQoL up to 12 months after surgery. 2 The differences in pain experience in individuals with depression compared to individuals without depression seem to be pronounced.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Comorbid conditions complicate and cause functional and emotional impairment in the daily life of men and women following cardiac surgery. 3 , 4 In our sample, both men and women reported associated back/neck problems, depression, and persistent pain intensity with lower HRQoL up to 12 months after surgery. 2 The differences in pain experience in individuals with depression compared to individuals without depression seem to be pronounced.…”
Section: Discussionmentioning
confidence: 68%
“…Despite research efforts, 6 8 it has been difficult to identify individuals who are susceptible to more severe postoperative pain than others. 7 Higher ratings of acute pain intensity and risk for persistent cardiac surgical pain have been linked to female sex, 9 11 younger age, 3 , 12 lower socioeconomic status (e.g., lower education, living alone), 11 comorbidities, 11 preoperative pain, 3 and analgesic consumption in the early postoperative phase. 9 , 11 However, individuals’ pain experiences also revolve around their response to psychological, social, and emotional stimuli, 6 which may explain variability in self-perceived pain sensitivity and why clinical and demographic factors are not consistently found to influence the risk for persistent surgical pain.…”
Section: Introductionmentioning
confidence: 99%
“…In favor of the particular trauma of sternotomy is evidenced by a pronounced pain syndrome, which is often chronic in nature and requires repeated use of analgesics. [1][2][3] Of a number of negative aspects of longitudinal median sternotomy, it is necessary to note a rather high incidence of postoperative proinflammatory complications, which, according to many studies, reaches up to 5%. 4,5 The most formidable of the infectious complications are mediastinitis and osteomyelitis of the sternum and ribs.…”
Section: Discussionmentioning
confidence: 99%
“…Sternotomy in the postoperative period can be cause of intense and prolonged pain syndrome. 1,2 Chronic pain syndrome after cardiac surgery can be one of the main factors worsening the general condition of patients, increases the rehabilitation period and worsens the quality of life. 3 Transsternal approach is also characterized by a rather high frequency of purulent postoperative complications.…”
Section: Introductionmentioning
confidence: 99%
“…A significant proportion of patients experience sternal pain and other associated neuro-musculoskeletal complications following median sternotomy which can impact upper limb and trunk function, activities of daily living and health-related quality of life. 15 To date, the predominant way of assessing function following cardiac surgery has not focused on specific evaluation of the site of surgery and the functional performance of the upper limb and thoracic region that is impacted by the procedure. 6,7 A review of the literature revealed that evaluation has focused on self-reported pain and quality of life or the use of shoulder outcome tools that target acute injury.…”
Section: Introductionmentioning
confidence: 99%